NEEDS: identidade visual e diretrizes da marca para o design system do NEES - ALVES, Taylor Costa (2025)
The objective of this work was to develop the visual identity and guidelines manual for NEEDS, the Design System of the Center for Excellence in Social Technologies (NEES), linked to the Institute of Computing at UFAL. Based on a theoretical study of visual identity, with the support of renowned authors and research applied to the NEES context, the essential visual elements for a solid and consistent brand were developed. The process included research and design phases, in addition to the creation of practical materials, such as presentation templates, a website inter face with design variations, and a detailed visual identity manual. In the end, the work resulted in the construction of a cohesive visual system, with materials approved and validated by NEES, which will serve as a reference to maintain the NEEDS visual standard and ensure its effective implementation in digital touchpoints.